2000
DOI: 10.1016/s0014-5793(00)01514-3
|View full text |Cite
|
Sign up to set email alerts
|

Highly divergent sequences of the pollen self‐incompatibility (S) gene in class‐I S haplotypes of Brassica campestris (syn. rapa) L

Abstract: Highly divergent sequences of the pollen self-incompatibility (S) gene in class-I S haplotypes of Brassica campestris (syn. rapa) L. Edited by Ulf-Ingo Flu « gge Abstract Self-incompatibility (SI) enables flowering plants to discriminate between self-and non-self-pollen. In Brassica, SI is controlled by the highly polymorphic S locus. The recently identified male determinant, termed SP11 or SCR, is thought to be the ligand of S receptor kinase, the female determinant. To examine functional and evolutionary pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
72
0
2

Year Published

2002
2002
2021
2021

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 111 publications
(79 citation statements)
references
References 38 publications
2
72
0
2
Order By: Relevance
“…Both SRK and SCR exhibit an extraordinarily high degree of DNA and protein sequence variability. Furthermore, the number of S locus variants, or S haplotypes, and consequently of SRK and SCR alleles, is typically large, with as many as 100 S haplotypes occurring in one species (9), and these polymorphisms are estimated to be at least 20-40 million years old (10). These features are consistent with the expectation that new SI variants have a strong reproductive advantage and persist in populations for long periods.…”
supporting
confidence: 53%
“…Both SRK and SCR exhibit an extraordinarily high degree of DNA and protein sequence variability. Furthermore, the number of S locus variants, or S haplotypes, and consequently of SRK and SCR alleles, is typically large, with as many as 100 S haplotypes occurring in one species (9), and these polymorphisms are estimated to be at least 20-40 million years old (10). These features are consistent with the expectation that new SI variants have a strong reproductive advantage and persist in populations for long periods.…”
supporting
confidence: 53%
“…Some of our DEFL genes could be involved in reproductive regulation as are members of the stig1 gene family (Goldman et al, 1994), or the Sterility-locus (S-locus) Cys-rich (SCR; Schopfer et al, 1999) and related pollen coat proteins (Watanabe et al, 2000). Beginning with the male determinant of sporophytic self-incompatibility (SSI), SP11 (a SCR protein), Vanoosthuyse et al (2001) used iterative BLAST searches to discover 37% of the peptides we identified.…”
Section: Defls May Have Functions Unrelated To Defensementioning
confidence: 99%
“…Beginning with the male determinant of sporophytic self-incompatibility (SSI), SP11 (a SCR protein), Vanoosthuyse et al (2001) used iterative BLAST searches to discover 37% of the peptides we identified. SP11 adopts the same three-dimensional fold as many defensins (Chookajorn et al, 2004) and displays high levels of divergent selection and allelic diversity (Watanabe et al, 2000). Binding of SP11 from selfpollen to the stigma-specific S-locus receptor kinase (SLK) starts the cascade of responses that leads to rejection.…”
Section: Defls May Have Functions Unrelated To Defensementioning
confidence: 99%
“…These cDNA clones were encoding genes related to secondary metabolism (Group 2: chalcone synthase, Group 9: flavonone-3-hydroxylase), transcription (Group 517: Myb26 protein, Group 554: MADS-box protein, GDEF1, Group 606: MADS box 26 protein), signal transduction (Group 642: protein kinase), hypothetical protein (Group 6, Group 16) and human disease associated protein (Group 170: cleft lip and palate associated transmembrane protein-like protein). In order to perform RT-PCR analysis, mRNA isolated from anthers from mature flower buds, anthers from immature flower buds, pistils from mature flower buds, pistils from immature flower buds, and leaves were reverse-transcribed by using the First-Strand cDNA synthesis kit (Amersham-Pharmacia, Uppsala, Sweden), as described in Watanabe et al (2000). The first strand cDNA was then used as a template for PCR amplification with a set of primers, Not I-dT and a specific primer to each gene.…”
mentioning
confidence: 99%